2022
DOI: 10.12973/ijem.8.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes Finding Nothing is Something: Shrinking the Gap between Emerging Bilingual Learners and English Fluent Students (Case in Point)

Abstract: <p style="text-align: justify;">For United States of America (USA) and other developed countries, science achievement gaps begin to emerge in elementary and primary school. Such gaps between USA student groups typically are connected to socio-economic status (SES) and issues such as students still learning the English language. Through an experimental design, this National Science Foundation funded study explores how integrating the arts into science, technology, engineering, and mathematics (STEM) curri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…That the lower fidelity implementation of STEAM before STEM was still significantly effective for EB students despite poor implementation, may suggest that a strong compensating STEAM first order effect advantage is possibly involved in the implementation system for this EB population of learners specifically, supporting the claim that a STEAM first order effect increases the EB students' opportunity to learn science. If equity building is of concern to curriculum designers, then teaching science through the arts with STEAM lessons is an effective approach (Corrigan et al, 2022), and introducing STEM units with STEAM may effectively improve the outcomes Page 16 of 19 Hughes et al International Journal of STEM Education (2022) 9:58 further for teaching life and physical sciences with the STEAM first order effect advantage. With limitations such as ensuring greater implementation fidelity, small-to-large effect sizes identified and cell size issue challenges due to random sampling methods, future research controlling for such methodological limitations further exploring these variables will be beneficial to determining more conclusive empirical results on inquiry-based and arts-based approaches collectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That the lower fidelity implementation of STEAM before STEM was still significantly effective for EB students despite poor implementation, may suggest that a strong compensating STEAM first order effect advantage is possibly involved in the implementation system for this EB population of learners specifically, supporting the claim that a STEAM first order effect increases the EB students' opportunity to learn science. If equity building is of concern to curriculum designers, then teaching science through the arts with STEAM lessons is an effective approach (Corrigan et al, 2022), and introducing STEM units with STEAM may effectively improve the outcomes Page 16 of 19 Hughes et al International Journal of STEM Education (2022) 9:58 further for teaching life and physical sciences with the STEAM first order effect advantage. With limitations such as ensuring greater implementation fidelity, small-to-large effect sizes identified and cell size issue challenges due to random sampling methods, future research controlling for such methodological limitations further exploring these variables will be beneficial to determining more conclusive empirical results on inquiry-based and arts-based approaches collectively.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from Wong et al (2022) showed that teachers felt more confident and self-efficacious to implement STEAM pedagogies in the classroom after completing a 10-week online professional development that specifically focused on supporting teachers' content knowledge and STEAM teaching perceptions. Drawing on a similar teacher-learner observer professional development model (Corrigan et al, 2022;Wong et al, 2022), this study also supported teachers in 40 h of face-to-face professional development on how to implement both STEAM and STEM pedagogical strategies with a major emphasis on supporting diverse learners in the classroom. As such, we might attribute the results of high fidelity implementing teachers and their success on EB and EF students to the quality of PD support teachers received.…”
Section: Rq3) To What Extent Does Implementation Fidelity Contribute ...mentioning
confidence: 93%